Frequency of Cystic Fibrosis Transmembrane Conductance Regulator Variants in Individuals Evaluated for Primary Ciliary Dyskinesia - Hannah, William B.; Truty, Rebecca; Gonzales, Virginia; Kithcart, Gregory P.; Ouyang, Karen; Zeman, Michelle K.; Li, Chun; Drumm, Mitchell; Nykamp, Keith; Gaston, Benjamin M. (The Journal of pediatrics, 2019)
To evaluate whether cystic fibrosis transmembrane conductance regulator (CFTR) variants are more common among individuals tested for primary ciliary dyskinesia (PCD) compared with controls. Data were studied from 1021 individuals with commercial genetic testing for suspected PCD and 91 777 controls with genetic testing at the same company (Invitae) for symptoms/diseases unrelated to PCD or CFTR testing. The prevalence of CFTR variants was compared between controls and each of 3 groups of individuals tested for PCD (PCD-positive, -uncertain, and -negative molecular diagnosis). The prevalence of 1 pathogenic CFTR variant was similar among the individual groups. When combining the PCD-uncertain and PCR-negative molecular diagnosis groups, there was a higher prevalence of single pathogenic CFTR variants compared with controls (P = .03). Importantly, >1% of individuals who had negative genetic testing results for PCD had 2 pathogenic CFTR variants (8 of 723), and the incidence of cystic fibrosis (CF) (2 pathogenic variants) is roughly 1 in 3000 individuals of Caucasian ethnicity (∼0.03%). This incidence was also greater than that of 2 pathogenic CFTR variants in the control population (0.09% [84 of 91 777]; P = 9.60 × 10−16). These variants correlate with mild CFTR-related disease. Our results suggest that a single pathogenic CFTR variant is not likely to be a PCD-mimetic, but ongoing studies are needed in individuals in whom PCD is suspected and genetic testing results are uncertain or negative. Furthermore, CF may be misdiagnosed as PCD, reflecting phenotypic overlap. Among individuals evaluated for PCD, CF should be considered in the differential even in the CF newborn screening era.